Formulasi Edible Film Berbasis Pati Biji Durian Dengan Penambahan Vco (Virgin Coconut Oil) dan CMC (CARBOXYMETHYL CELLULOSE) Menggunakan Desain Eksperimen Faktorial 2k - Adam, Budiyanto; Kasim, Rahmiyati; Ahmad, Lisna (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Innovation of edible film made from durian seed starch is done in addition to the price is affordable, easy to obtain and contains amylose by 26.6% so that it can form a film. The purpose of this study was to determine the best formula of durian seed starch-based edible film with a combination of VCO and CMC on the characteristics of durian seed starch edible film. This study used a 2k factorial experimental design consisting of 3 factors of durian seed starch concentration with a range of 1 - 10% (w/v), VCO 0.3 - 1.5% (v/v) and CMC 0.1 - 1% (w/v), while water vapor permeability, absorption and film thickness as response variables. The results stated that the relationship between all independent variables (starch, VCO, and CMC) can be described in the form of a linear model (P < 0.05). The concentration of durian seed starch interacted with CMC only affected the film thickness. The concentration of VCO showed a positive influence on the decrease of water vapor permeability and absorption water.